Integrating Conservation and Development in Protected Area Management - can we do It?. - Badola, Ruchi; Bhardwaj, A. K.; Mukherjee, S. K. (Indian Forester, 2000)
The Protected Area (PA) Network in India has helped to conserve a significant part of India's biodiversity. It has, however, engendered conflicts between the livelihood requirements and aspirations of the local communities living in and around these areas, and PA ma,nagers. The stress has been on reducing or eliminating altogether the human sources of biotic pressures, with the assumption that any such pressure was detrimental to wildlife interests. Although such an approach to conservation has been successful to a certain extent, it also alienated the local people from the PAs. Enlisting the cooperation and support of local people has thus, emerged as a major priority area of in situ biodiversity conservation. This is the concept of ecodevelopment as it is referred to in India or Integrated Conservation and Development in many other countries. Ecodevelopment, addressed the livelihood problems of people surrounding PAs, using as its basic thrust the diversion of as much pressure from PAs all possible. However with almost a decade of experience with ecodevelopment, there is now a focus on collaborative management or Joint Protected Area Management as it is referred to, which envisages the involvement of local communities and other stakeholders in PA management. This paper discusses the concept of ecodevelopment, its ev01ution and the problems associated with developing collaborative partnerships with different stakeholders. It examines some of the recent models of community participation in PA management across the country. Besides a strong policy and legal support, other factors like strong conservation-development linkages, trained and motivated manpower and a strong research base and regular monitoring playa role in its success. The paper goes on to conclude that in order to ensure the sustainability of such programs, the logical outcome of ajoint management approach and the rights and responsibilities of the local communities and other stakeholders should be clarified. The integration of the PAs into landscape or regional level planning by a comprehensive review of the national and state laws relating to natural resources is required.